1997
DOI: 10.1002/(sici)1097-0142(19970601)79:11<2137::aid-cncr11>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Response to second‐line chemotherapy in patients with metastatic breast carcinoma previously responsive to first‐line treatment

Abstract: METHODS.ment. A better response rate to second-line chemotherapy was observed in patients with the following features: 1) chemotherapy free time (time between onset of metastatic disease and initiation of first-line) õ 12 months (P Å 0.03); 2) complete response to first-line chemotherapy (P Å 0.013); 3) response duration to first-line chemotherapy ú 14 months (P Å 0.0001); 4) progression free interval (time between end of first-line treatment and initiation of second-line chemotherapy) ú 11 months (P Å 0.0001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Realworld studies indicate that response rates [11,13,[43][44][45][46][47][48][49][50] and TTP or treatment failure [11,[17][18][19][20][21][43][44][45][46][47][48]50,51] decline with subsequent chemotherapy lines. Additionally, response to and/or longer TTP or PFS of previous chemotherapy significantly influenced time to progression or PFS on next-line chemotherapy within multivariate analyses [12,17,18,45,47,[49][50][51][52]. In our current study, a TTP of >10 months in first-line was associated with better PFS in second-line study treatment (Table 2).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Realworld studies indicate that response rates [11,13,[43][44][45][46][47][48][49][50] and TTP or treatment failure [11,[17][18][19][20][21][43][44][45][46][47][48]50,51] decline with subsequent chemotherapy lines. Additionally, response to and/or longer TTP or PFS of previous chemotherapy significantly influenced time to progression or PFS on next-line chemotherapy within multivariate analyses [12,17,18,45,47,[49][50][51][52]. In our current study, a TTP of >10 months in first-line was associated with better PFS in second-line study treatment (Table 2).…”
Section: Discussionmentioning
confidence: 57%
“…In comparison, trials reporting second-line PFS within this review were scarce, and medians varied from 2.5 to 9.8 months depending on the investigated single-agent [10]. Observational studies on multiple lines of chemotherapy for advanced breast cancer reported median second-line PFS or TTP between 2.5 and 11.7 months [11][12][13][14][15][16][17][18][19][20][21]. However, comparison of these outcomes between trials is limited due to the large variety in (amount of) previous treatments, selection of patients, type of chemotherapy and whether or not concurrent treatments were given.…”
Section: Discussionmentioning
confidence: 92%
“…En étude multifactorielle, l'intervalle libre prédit l'efficacité du traitement de rattrapage (22). Ici encore, la monochimiothé-rapie, notamment par taxane, devrait être envisagée en tenant compte de l'index thérapeutique (17,23).…”
Section: Traitements En Phase Palliative Activeunclassified